GROSIFIKASI IDEOLOGI RASA DALAM PERKEMBANGAN SENI LUKIS BALI - I Ketut Suwidiarta (Pascasarjana Universitas Hindu Indonesia, 2017)
The focus of this article is the past orientation or idea of the Balinese in painting. The process of grosification of the artistic ideology occurs since the tourism has developed in Bali and the implications of the grossification of the taste ideology on the painting emerging today. The purpose of this article is to present and comprehensively describe the taste grosification in the Balinese painting so that people can assess, sort and get inspired on how to develop the fine arts for the future time ideals.